2015
DOI: 10.7441/joc.2015.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Does the EU Funding Increase Competitiveness of Firms by Supporting Organisational Changes?

Abstract: Competitive firms with a good economic performance contribute to social development and quality of life. Countries and regions support competitiveness of firms through public policies and public funds. The research concerns question whether financial support from public funds actually helped to increase competitiveness in firms through organisational changes. This paper explores the relationship between competitiveness of firms (measured by sales divided by employment) with organisational structure changes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Based on the research concerning highly developed economies one can point out a few most significant segments of national institutional systems that determine productivity growth, thus long term well-being of societies, in the reality of the global knowledge-based economy (Balcerzak, 2015;Balcerzak and Pietrzak, 2016c). The crucial role is given to the system of regulations that influence the incentives for entrepreneurship and the effectiveness of financial systems institutions that together create the framework for high supply of enterprises with high growth potential (Felipe and Oto, 2015;Zineker et al, 2013;Zinecker and Bolf, 2015;Meluzín and Zinecker, 2016;Fałdziński et al, 2016). These enterprises are responsible for providing new technological and organizational solutions giving the base for productivity growth.…”
Section: The Main Determinants Of Quality Of Institutions For Global mentioning
confidence: 99%
“…Based on the research concerning highly developed economies one can point out a few most significant segments of national institutional systems that determine productivity growth, thus long term well-being of societies, in the reality of the global knowledge-based economy (Balcerzak, 2015;Balcerzak and Pietrzak, 2016c). The crucial role is given to the system of regulations that influence the incentives for entrepreneurship and the effectiveness of financial systems institutions that together create the framework for high supply of enterprises with high growth potential (Felipe and Oto, 2015;Zineker et al, 2013;Zinecker and Bolf, 2015;Meluzín and Zinecker, 2016;Fałdziński et al, 2016). These enterprises are responsible for providing new technological and organizational solutions giving the base for productivity growth.…”
Section: The Main Determinants Of Quality Of Institutions For Global mentioning
confidence: 99%
“…The emphasis is put on improvement of R&D, and innovation funding, which happens to be one of the objectives in Europe 2020 Strategy for improving competitiveness of the EU (Martinez & Potluka, 2015). The ambition is to ensure public and private investment in order to achieve 3% of GDP (EC, 2010).…”
Section: Randd Expenditures and Innovations In The Eu Contextmentioning
confidence: 99%
“…It was also determined that EU structural funds have significant influence on infrastructure and macroeconomic, scientific and social environment (Remeikiene & Gaspareniene, 2016). Research in the Czech Republic showed that only European Social Fund has helped to increase productivity (Martinez & Potluka, 2015). The authors that researched the export competitiveness and productivity in Lithuania, argue that the export competitiveness is a derivative of main factors' productivities (Travkina & Tvaronaviciene, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%